Analysis of the Effect of Supply Chain Management and Local Wisdom on the Competitiveness of Coastal Fishing Communities in North Minahasa District (International Journal of Scientific Research and Management (IJSRM), 2023)
Supply Chain Management is an integrative method or approach to manage the flow of products, information, and money in an integrated manner involving parties from upstream to downstream consisting of suppliers, factories, distribution networks and logistics services. The supplier is one of the most important links in determining product quality and the speed with which the product reaches the consumer. In the capture fisheries industry in North Sulawesi, coastal fishing communities in North Minahasa District are one of the spearheads of the success of the supply chain for the capture fisheries industry because they function as suppliers for the fish processing industry in North Sulawesi. The purpose of this study was to analyze the influence of Supply Chain Management, namely the variables of technical and managerial assistance, information sharing, trust, long-term relationships, and process integration on the competitiveness of coastal fishing communities in North Minahasa District and local wisdom on competitiveness. This research uses causal associative research. The analytical method used is Multiple Linear Regression Analysis. The results showed that technical and managerial assistance, information sharing, trust and local wisdom had a significant effect on the competitiveness of coastal fishing communities in North Minahasa District, while long-term relationship variables and process integration did not significantly affect the competitiveness of coastal fishing communities in North Minahasa District.